Theoretical principles of petroleum hydrogeology of the West Siberian megabasin (WSMB) - Matusevich, V.; Popov, Viktor Konstantinovich; Kovyatkina, L.; Pozdeeva, Galina Petrovna (IOP Publishing, 2016)
Comprehensive study of the chemical and gas composition, temperatures, levels, pressure of deep underground water in deep wells is associated with the beginning of the systematic development of the oil and gas potential in Western Siberia and the first discovery of large deposits here. The development of new branches of hydrogeology is due to the fact of more and more available data. Thus, fundamental understandings of the WSMB hydrogeological conditions are being translated into new theories. Geodynamically, the WSMB structure was revised and based on hydrogeological data, regional and local prediction of oil and gas occurrence exploration criteria were developed. Based on the dispersion halo water-dissolved substance theory, exploration methodology of "neglected" deposits were formulated, conceptual issues of technogenic changes of oil and gas hydrogeosphere areas were being developed.
Keywords: гидрогеология; Западно-Сибирский бассейн; скважины; нефти; газы; гидрогеологические условия; гидрогеологические данные; запасы; геологоразведочные работы